Declining rates of sterilization procedures in Western Australian women from 1990 to 2008: The relationship with age, hospital type, and government policy changes - Jama-Alol, K.; Bremner, A.; Stewart, L.; Kemp-Casey, A.; Malacova, E.; Moorin, Rachael; Shirangi, A.; Preen, D. (Elsevier, 2015)
Objective: To describe trends in age-specific incidence rates of female sterilization (FS) procedures in Western Australia and to evaluate the effects of the introduction of government-subsidized contraceptive methods and the implementation of the Australian government's baby bonus policy on FS rates. Design: Population-based retrospective descriptive study. Setting: Not applicable. Patient(s): All women ages 15-49 undergoing an FS procedure during the period January 1, 1990, to December 31, 2008 (n = 47,360 procedures). Intervention(s): Records from statutory statewide data collections of hospitals separations and births were extracted and linked. Main Outcome Measure(s): Trends in FS procedures and the influence on these trends of the introduction of government policies: subsidization of long-acting reversible contraceptives (Implanon and Mirena) and the Australian baby bonus initiative. Result(s): The annual incidence rate of FS procedures declined from 756.9 per 100,000 women in 1990 to 155.2 per 100,000 women in 2008. Compared with the period 1990-1994, women ages 30-39 years were 47% less likely (rate ratio [RR] = 0.53; 95% confidence interval [CI], 0.39-0.72) to undergo sterilization during the period 2005-2008. Adjusting for overall trend, there were significant decreases in FS rates after government subsidization of Implanon (RR = 0.89; 95% CI, 0.82-0.97) and Mirena (RR = 0.81; 95% CI, 0.73-0.91) and the introduction of the baby bonus (RR = 0.70; 95% CI, 0.61-0.81). Conclusion(s): Rates of female sterilization procedures in Western Australia have declined substantially across all age groups in the last two decades. Women's decisions to undergo sterilization procedures may be influenced by government interventions that increase access to long-term reversible contraceptives or encourage childbirth.